The Impact of Cervical Cancer on the Sexuality of Muslim Female Patients with Husbands: A Qualitative Phenomenological Study - Distinarista, Hernandia; Rahayu, Tutik; Wuriningsih, Apriliani Yulianti; Wahyuni, Sri (South East Asia Nursing Research, 2023)
The treatment period for the cancer cervix and its treatment can also cause various change physical and physiological, which can cause various problems one of which is the disturbance of sex. Cancer cervix in a manner directly affects the sexual organs, almost 50% of women with cancer cervix report dysfunction sexual. Dysfunction sexual This can be felt only by women just or women with a partner. Study This aim to see the aspect of sexuality specifically for patients with cancer cervix, based on a change in physical and psychological consequences of the disease and its treatment. This study used a phenomenological hermeneutic method, data collection was carried out using semi-structured interviews which were then transcribed. Data analysis using content analysis or content analysis. Research results obtained three themes namely: problem physical problems psychologically, the efforts made to overcome the problem with sex, and hope patience. Deep conclusions study this patient’s cancer cervix experience problem sexual dysfunction and need maintenance holistically.